Tree removal in development site: experience and perception of landscape professionals / Khalilah Hassan, Ramly Hasan and Wan Saiful Nizam Wan Mohamad - Hassan, Khalilah; Hasan, Ramly; Wan Mohamad, Wan Saiful Nizam (2022)
Tree removal in urban areas is among the activities that contribute to the loss of urban trees. An understanding of the motives for tree removal actions in development areas is necessary so that the loss of valuable urban trees can be avoided. The results of this study provide an initial overview of the retention practices and reasons for tree removal in development areas. A total of 30 landscape professionals including academicians, consultants, and public officials were questioned about their experience and perceptions of tree retention practices through surveys and interviews. Survey data were analyzed using SPSS software and descriptive statistics by finding each item statement's frequency and mean value. The results of the study showed that 80% of the respondents thought that existing trees were usually removed in development areas. This study found that the main reason for tree removal, based on the mean ranking, is that "not everyone understands and appreciates trees" (mean = 4.73, rank 1), followed by "transplanting trees requires expertise" (mean = 4.60, rank 2). The reasons of "lack of awareness and understanding of existing laws or regulations" and "fear of falling trees" (mean = 4.37, rank 3), respectively. The main finding of this study suggests that the tree removal decisions are influenced by the level of knowledge of trees and related legislation by the various professionals involved in a development project. The knowledge simultaneously affects the awareness and perception of the survival of the tree to be retained in the development site.